DINÂMICA DA OCUPAÇÃO DO SOLO DA BACIA DO RIO ITIQUIRA, MATO GROSSO, BRASIL - OKA-FIORI, Chisato; FIORI, Alberto Pio; HASUI, Yociteru (Ra’e Ga: o Espaço Geográfico em Análise, 2003)
A área de estudo corresponde à bacia do alto curso do rio Itiquira, totalizando 5.361km2. Nesta área foi feito o estudo da dinâmica ambiental com emprego de técnicas SIG e imagens de satélite dos anos de 1966, 1985 e 1996. A análise da dinâmica ambiental envolveu o estudo das modificações no uso e ocupação do solo nos 30 anos considerados, mostrando que a bacia do rio Itiquira sofreu grande impacto no uso e ocupação do solo no período compreendido entre 1966 e 1996. Em 1966, as áreas de vegetação natural (matas e cerrados) ocupavam 90,64% do total da área, reduzindo-se para 60,57% em 1985 e para apenas 36,66% em 1996. Nesse processo, 289.382ha, de um total de 485.928ha de cobertura vegetal natural, foram perdidos como tal. Em 30 anos houve um aumento de 313.725ha de terras cultivadas, correspondendo a cerca de 113 vezes a ocupação de terras do ano de 1966 (2.798ha). Dynamics of soil occupation of the river Itiquira basin, Mato Grosso, Brazil Abstract The study area corresponds to the basin of the Itiquira river high course, totalling 5,361km2. In this area a study of the environmental dynamics was made, applying SIG techniques and satellite images of the years 1966, 1985 and 1996. In 1966 the areas of natural vegetation (forests and groves) occupied 90.64% of the total of the area, which was diminished to 60.57% in 1985 and to only 36.66% in 1996. In this process, 289,382ha of a total of 485,928ha of natural vegetal covering had been lost. At the same time, the agrarian surfaces (agriculture and pasture) that occupied only 0.52% of the total area in 1966, increased to 34.89% in 1985 and to 59.04% in 1996. In 30 years there was an increase of 313,725ha of cultivated lands, corresponding to about 113 times the land occupation of the year of 1966 (2,798ha). The areas classified as urban show a gradual increase since 1966, from 39ha in 1996 to 58ha in 1985, and to 178ha in 1996. The other classes of soil use and occupation (reforestement areas, uncovered and affected by fire and humid areas) added were smaller than 4,27% in 1996.